1986
DOI: 10.1085/jgp.88.2.237
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation of two distinct K conductances in the basolateral membrane of turtle colon.

Abstract: The K conductance of the basolateral membrane of turtle colon was measured in amphotericin-treated cell layers under a variety of ionic conditions . Changing the composition of the bathing solutions changed not only the magnitude but also the physical properties of the basolateral K conductance. The results are consistent with the notion that altered ionic environments can lead to changes in the relative abundance of two different populations of K channels in the basolateral membrane, which can be differentiat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

1991
1991
1997
1997

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(21 citation statements)
references
References 29 publications
0
21
0
Order By: Relevance
“…9). (Germann, Lowy, Ernst & Dawson, 1986;Ishikawa & Cook, 1993). The blocker sensitivity of the frog proximal tubule reported here, where one conductance was inhibited by Ba2+ and quinidine, and the second by quinidine alone, is in direct contrast to turtle colon, in which two types of channel were inhibited by BaP, only one being inhibited by quinidine (Germann et al 1986).…”
Section: Single Channel Currentsmentioning
confidence: 67%
“…9). (Germann, Lowy, Ernst & Dawson, 1986;Ishikawa & Cook, 1993). The blocker sensitivity of the frog proximal tubule reported here, where one conductance was inhibited by Ba2+ and quinidine, and the second by quinidine alone, is in direct contrast to turtle colon, in which two types of channel were inhibited by BaP, only one being inhibited by quinidine (Germann et al 1986).…”
Section: Single Channel Currentsmentioning
confidence: 67%
“…The sudden appearance of these channels in inside-out patches immediately after patch excision into a Ca2+-containing medium was the first indication that the Quinidine and lidocaine were also tested on the inward-rectifying K+ channel as these agents selectively block one type of macroscopic K+ conductance in the turtle colon (Germann, Ernst & Dawson, 1986 a;Germann, Lowy, Ernst & Dawson, 1986b) and also block the single channels thought to be responsible for that conductance (Richards & Dawson, 1986). As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…One population of basolateral K+ channels appears to mediate the recycling of K+ necessary to maintain electrogenic Na+ absorption (Germann, Ernst & Dawson, 1986a) and is blocked by DPC (Richards & Dawson, 1989) but not by serosal TEA+ up to 20 mM (Germann et al 1986b). Another distinct population appears to mediate swellinginduced basolateral K+ exit (Germann et al 1986a) and is blocked by quinidine and lidocaine (Richards & Dawson, 1986) but not by up to 20 mm TEA' (Germann et al 1986b). Blockade of these channels by lidocaine also induces current fluctuations that produce a Lorentzian component in the PDS (Dawson, Van Driessche & Helman, 1988).…”
Section: Tea+-sensitive Apical K+ Channels Mediate Active K+ Secretionmentioning
confidence: 99%
“…Those results suggested that K+ exited the epithelial cells via a population of K+-permeable channels in the apical membrane, although the mechanism for inhibition by amiloride was not clear. Turtle colon is also well suited for a comparison between apical and basolateral K+ channels because several populations of basolateral K+ channels have been identified and can be distinguished by blocker specificity (Germann, Lowy, Ernst & Dawson, 1986b;Chang & Dawson, 1988;Richards & Dawson, 1989).…”
Section: Introductionmentioning
confidence: 99%